Different approaches in determining the vertical and horizontal jaw relations during complete denture fabrication – a literature review - Zielke, Maria; Jasnoch, Joanna; Maciejewska, Izabela (Journal of Stomatology, 2021)
Recording the jaw relations is a critical step during the fabrication of complete dentures. Both vertical and horizontal relations must be correctly established to ensure efficient function of the complete dentures with the least amount of trauma to the supporting tissues and temporomandibular joints (TMJs). The aim of this review was to collect comprehensive data about the most recommended methods for determining the optimal vertical dimension of occlusion (VDO) during the fabrication of complete dentures and to determine whether and/or to what extent these methods respect the correct spatial relations in TMJs. An electronic search through the PubMed, Web of Science, OVID, SCOPUS and EBSCO search engines selected 111 references from peer-reviewed journals, which met the inclusion criteria for this literature review. The single, exclusive and scientifically confirmed consensus for the determination of both the VDO and centric relation during complete denture fabrication is still lacking. Authors agree that the establishment of an incorrect relation between the maxilla and mandible causes severe, mostly harmful consequences in the stomatognathic system. So far the available procedures are associated with a high degree of subjective clinical judgements and variability. Thus, ongoing studies with the application of new technologies are still current and strongly recommended.